SWiFiNet: a real field WSN testbed. (1st January 2013) - Rohankar, A.W.; Naskar, Mrinal Kanti; Mukherjee, Amitava
Proliferation of technologies and services related with wireless sensor network has made a great impact on all aspects of life. Research and development in this domain naturally calls for real-time WSN testbeds. Present day WSN testbeds are expensive and complex in operation and simulators are unable to justify real-time field interaction. Design of SWiFiNet completely eliminates expensive back channel infrastructure for reprogramming, communication data logging and setting of test experimental setup control parameters. This has provided true real-time portability and testability of the network in field with around 90% reduction in testbed infrastructural setup cost. SWiFiNet is hardware and system software independent testbed. SWiFiNet permits time synchronised data recording, capturing, processing and repeatability of an experiment. Extensive experiment parameter configuration, wide scalability of the network, in-node status monitoring are significant features of SWiFiNet.